Bending tests on building beams containing electric arc furnace slag and alternative binders and manufactured with energy-saving placement techniques. (August 2021) - Santamaría, Amaia; García-Llona, Aratz; Revilla-Cuesta, Víctor; Piñero, Ignacio; Ortega-López, Vanesa
Graphical abstract: Highlights: High-workability green concretes manufactured with EAFS and alternative binders. Bending strength testing on twelve building beams made with sustainable concretes. Experimental deflections and neutral axis position accurately evaluated. Elastic behavior regarding deflections observed up to 80% of failure load. Designed beams fulfill the requirements of the most common calculation standards. Abstract: The environmental impact of the building sector is especially relevant during the construction phase. Both the materials and the construction methods that are currently in use must be reconsidered, in order to minimize the environmental impact of concrete-based structures. This research is therefore focused on achieving greener concrete-based building structures. In this context, the feasibility of careful use of materials for concrete manufacture and the use of construction techniques that can facilitate and reduce energy consumption during placement are both studied. To do so, twelve sample beams were prepared using eight different sustainable high-workability structural concretes. The aim was to maximize the use of the by-products that amounted to over 80% of the concrete mass, steelmaking slags, fly ash, and quarry waste, and to employ energy-saving concrete placement techniques. The beams underwent bending tests in which their mechanical behavior and their compliance with the specifications of the most relevant building codes were verified. The results pointed to the feasibility of increased sustainability in the field of building engineering through the suitable use of selected by-products and techniques.